Farmers' market voucher programs in the United States and Canada: benefits and opportunities - Kinnard, Kristin, author (Colorado State University. Libraries, 2014)
Farmers' Market Nutrition Programs (FMNPs) in the United States and Canada are designed to provide nutrition assistance and nutrition education to low-income families, while supporting and promoting domestic agriculture. This paper examined the current scientific literature on the benefits of the programs to coupon recipients and farmers, as well as the influence of education interventions on nutrition knowledge. Coupon recipients were found to increase their fruit and vegetable consumption through the use of the programs, as well as their nutrition knowledge, and farmers were found to increase their income. FMNPs were determined to be effective at achieving their goals and worthy of continued funding. Suggestions are included to improve coupon redemption rates to maximize the benefits of the programs to all participants, and system infrastructure is suggested for Canadian markets to facilitate the reception of provincial funding, in order to create program growth to benefit more individuals, families, and farmers.
Professional Paper, Agricultural Extension Education.